NEED ANALYSIS OF CASE-BASED (CREATIVE, ACTIVE, SYSTEMATIC, EFFECTIVE) TEACHING MATERIALS TO IMPROVE STUDENTS' PROBLEM SOLVING AND CREATIVE THINKING ABILITY - Ningsih, Widia (Jurnal Pelita Pendidikan, 2024)
The development of open materials is necessary to improve their The Development of teaching materials is necessary to improve student understanding. However, the existing teaching materials still have shortcomings, meaning they do not fully support the learning process in learning media courses. These weaknesses can be in the form of learning information presented that is not detailed, both in terms of material and visualization, or that some teaching materials are presented in a foreign language and are difficult to understand. Seeing these problems, the aim of this research is to analyze the needs for CASE-based teaching materials (Creative, Active, Systematic and Effective) in improving students' problemsolving and creative abilities in learning media courses. CASE (Creative, Active, Systematic and Effective) is intended to help students creatively, actively, systematically and effectively, resulting in successful achievement of learning objectives. In this situation, creativity refers to the ability to develop unique teaching materials that can motivate students to learn. The definition of creative thinking is the ability to create new correlations between various aspects, analyze them, and use conclusions to solve problems in certain learning. The subjects of this research are students of the Biology Education study program, Department of Biology, Medan State University class of 2020. The sample was randomly selected as many as 30 students. This research is a qualitative descriptive research oriented towards the development of a product. Data collection was carried out using interview sheets, observation sheets and questionnaires.